Propuesta de ubicación taxonómica para los chayotes silvestres (Sechium edule, Cucurbitaceae) de México - Lira, Rafael; Castrejon, Javier; Zamudio, Sergio; Rojas-Zenteno, Carlos (Instituto de Ecología, A.C., 1999)
In this paper a taxonomic classification for the chayote, Sechium edule (Jacq.) Swartz, that includes two subspecies: S. edule ssp. edule and S. edule ssp. sylvestre, is proposed. Additionally, wild populations of the species are documented for the first time for the states of Querétaro and Puebla, México, and distributional data for similar populations so far recorded in the country are also provided.